(untitled) (Bangladesh Journal of Pharmacology, 2014)
Neem (leaves, flowers, seeds etc.) have been used traditionally against many diseases. We, thus, investigated the antimicrobial effect of ethanolic neem leave extract on Klebsiella, Salmonella and Staphylococcus aureus and found its growth inhibitory effect on Klebsiella and Salmonella at the concentration of 12.5 mg/mL and 6.2 mg/mL respectively with average diameter of zone of inhibition 18 mm and 20 mm respectively. It failed to inhibit the growth of Staphylococcus aureus at the highest concentration used (50 mg/mL). Findings of this preliminary experimental study suggest that, neem can be tried against Klebsiella and Salmonella showing limited efficacy.